The global economic impact of politicians: Evidence from an international survey RCT - Dorine Boumans; Klaus Gründler; Niklas Potrafke; Fabian Ruthardt (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We use the US presidential election on 3 November 2020 to examine how the US president influences economic expectations of international experts. We design a large-scale RCT among 843 experts working in 107 countries, asking about their expectations regarding GDP growth, unemployment, inflation, and trade in their country. The sample is split randomly in two subsamples. Half of the participants were surveyed closely before the election, the other half directly after Joe Biden had been called US president. Our results show that the election of Joe Biden increased growth expectations of international experts by 0.98 percentage points for the year 2021. We also find that (i) treatment effects materialize only in the short-run and (ii) experts' uncertainty increased after the election. Our results suggest that exceptional politicians influence global economic outcomes.
Keywords: A11; D72; O11; 330; US Presidential Elections; Politicians; Economic Expectations; EconomicExperts; Randomized Controlled Trial; Causal Inference